e*-Hollow-Lifting and Cofinitely e*-Lifting Modules - Hiba Baanoon; Wasan Khalid (Journal of the Indonesian Mathematical Society, 2022)
The novel ideas in module M over a ring R are introduced in this study. The first one, a generalization of the e∗-lifting module, is known as e∗-hollow-lifting. The second idea, an inference of e∗-lifting, is known as a cofinite e∗-lifting module. We shall demonstrate some of these ideas’ properties